2011
DOI: 10.1111/j.1863-2378.2009.01269.x
|View full text |Cite
|
Sign up to set email alerts
|

A Serosurvey of Crimean‐Congo Haemorrhagic Fever Virus in Dairy Cattle in Iran

Abstract: A seroepidemiological survey to determine the prevalence of Crimean-Congo haemorrhagic fever (CCHF) virus among dairy cattle in Iran was carried out during 2006 and 2008. Blood samples were collected from 876 animals in five different provinces of the country. Sera were tested by a sandwich enzyme-linked immunosorbent assay (ELISA) for quantitative determination of antibodies to CCHF virus. Serological evidence of infection was noted in 52 (5.9%) of 876 dairy cattle. Antibody prevalence increased with age; 78.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 11 publications
3
11
0
Order By: Relevance
“…We believe that the association of CCHFV infection rate and age is probably attributed to frequent exposure of older cattle to infected tick in the pasture. , 2008;Lotfollahzadeh et al, 2011). In addition, the study revealed significant association between heavily tick-infested cattle and CCHFV seropositivity.…”
Section: Discussionmentioning
confidence: 88%
“…We believe that the association of CCHFV infection rate and age is probably attributed to frequent exposure of older cattle to infected tick in the pasture. , 2008;Lotfollahzadeh et al, 2011). In addition, the study revealed significant association between heavily tick-infested cattle and CCHFV seropositivity.…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, young calves are usually kept indoors and are well taken care of by the animal owners from infectious diseases particularly, tick-borne infections. Previous epidemiological surveys indicated that there were higher risks of older cattle for CCHFV infections in different countries including Egypt, Iran and Turkey [20,23,31]. In addition, there was also a significant difference between the breed of the animal and CCHFV infection rate.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, all camels included in this study aged over one year. Therefore, it is assumed that maternal antibodies no longer persisted and that antibody indicated direct exposure to CCHFV [ 1 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%